2007
DOI: 10.1144/sp290.14
|View full text |Cite
|
Sign up to set email alerts
|

Transpressional structures on a Late Palaeozoic intracontinental transform fault, Canadian Appalachians

Abstract: The east-west Minas fault zone, separating the Early Palaeozoic Meguma and Avalon terranes of the Appalachians, experienced dextral strike-slip motion during the Carboniferous. Abundant oblique contractional structures indicate localized dextral transpression, immediately south of the zone, probably associated with a restraining bend. Subsurface data indicate that the deformed Horton Group clastic rocks are thrust above younger Windsor Group evaporites.Excellent exposures on wave-cut platforms of the Bay of Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Despite these arguments, McCutcheon and Robinson (1987) favored a rift model for the Maritimes Basin as a whole, whereas Martel (1987) favored a strike-slip origin for the Sackville basin, the depocenter immediately north of the Cumberland basin. Subsequent authors (e.g., Hyde et al, 1988;MacInnes and White, 2004;Waldron, 2004;Waldron et al, 2007;Murphy et al, 2011) have documented signifi cant strike-slip motion during deposition of various parts of the Maritimes Basin fi ll. Recently, Gibling et al (2008) compared the tectonic development of the Maritimes Basin with that of the eastern Mediterranean, and Hibbard and Waldron (2009) have suggested that subsidence in the Maritimes Basin was related to substantial (~250 km) dextral strike-slip motion throughout the Appalachians, which reactivated a promontory-reentrant system in the early Paleozoic Laurentian continental margin (Thomas, 1977(Thomas, , 1991 Lawrence, Grand Banks, and Cabot Strait (e.g., Durling and Marillier, 1993;Langdon and Hall, 1993;Brown, 1998;Pascucci et al, 1999).…”
Section: Maritimes Basin Tectonicsmentioning
confidence: 99%
“…Despite these arguments, McCutcheon and Robinson (1987) favored a rift model for the Maritimes Basin as a whole, whereas Martel (1987) favored a strike-slip origin for the Sackville basin, the depocenter immediately north of the Cumberland basin. Subsequent authors (e.g., Hyde et al, 1988;MacInnes and White, 2004;Waldron, 2004;Waldron et al, 2007;Murphy et al, 2011) have documented signifi cant strike-slip motion during deposition of various parts of the Maritimes Basin fi ll. Recently, Gibling et al (2008) compared the tectonic development of the Maritimes Basin with that of the eastern Mediterranean, and Hibbard and Waldron (2009) have suggested that subsidence in the Maritimes Basin was related to substantial (~250 km) dextral strike-slip motion throughout the Appalachians, which reactivated a promontory-reentrant system in the early Paleozoic Laurentian continental margin (Thomas, 1977(Thomas, , 1991 Lawrence, Grand Banks, and Cabot Strait (e.g., Durling and Marillier, 1993;Langdon and Hall, 1993;Brown, 1998;Pascucci et al, 1999).…”
Section: Maritimes Basin Tectonicsmentioning
confidence: 99%
“…thrust segments at the base of the ophiolitic blocks and steeplydipping, left lateral NNW-SSE ductile shear zones and major faults deformed most of the exposed lithologies and overprinted the preexisting lithologic/tectonic contacts. Second-order, sinistral shear zones form a positive flower structure (e.g., Clendenin, 1993;Waldron et al, 2007). The steeply dipping strike-slip fault segments bifurcate into reverse faults and then flatten into moderately dipping NNW-trending thrust zones.…”
Section: Geology and Structural Settingmentioning
confidence: 99%
“…16, inset). While the amount of convergence increases in transpression as predicted and discussed by many authors for the CRFZ, the size of the extensional sector associated with shearing gets smaller but never entirely disappears (Waldron et al, 2007) A component of right-lateral strike-slip motion cannot be ruled out for this family of linear, east-west trending faults that includes the NDRFZ. Some of these secondary faults, in conjunction with the main CRFZ, define or bound localized and elevated blocks of highly deformed pre-middle Miocene rocks (Fig.…”
Section: Role Of East-west Faults Along the Crfzmentioning
confidence: 56%
“…9, 11, and 13 are oriented according to the direction of either predicted synthetic strike-slip faults or normal faults. Waldron et al (2007) has noted that extension in strike-slip and transpressional basinal settings can be a large component of the deformation and is often overlooked in outcrop settings where exposures are commonly discontinuous.…”
Section: Role Of Ndrfz To Deformation Process Along the Crfzmentioning
confidence: 99%